Pengaruh Metode Pembelajaran dan Pemahaman Konsep Sejarah Terhadap Hasil Belajar Sejarah Mahasiswa FIPS Program Studi Pendidikan Sejarah IKIP-PGRI Pontianak - Pujo Sukino (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2014)
Abstract This aims to find out effect of intructional methods and concept understanding on the outcomes of history learning on the student. The research was conducted in IKIP-PGRI Pontianak.The methodology used is the experiment was conducted using treatmen by level 2x2. The research date was taken from the observation, tests and questionnaires Sample size 44 student selected randomly. The results showed that. 1). History learning outcome of students using inkuiri intructional method are higher than those students using conventional intructionalmethod, 2). There is interaction effect between intructional method and understanding on history learnig outcome of students; 3 ). Results studied history student given method of intructionalinkuiri with have understanding concept high higher of the students given method of intructional conventional with have understanding concept high. 4 ). Results studied history student given method of intructional inkuiri with haveunderstanding concept lower of lower of student who uses the method of intructionalconventional with have understanding concept low. Keywords : Concept Understanding, Intructional Methods, Outcome Learning